931. Telemedicine for the Treatment of Hepatitis C: A Systematic Review and Meta-Analysis. (26th November 2018) - De Gijsel, David; Kruger, Blake; Hakim, Dema; Moore, Sarah
Abstract: Background: Hepatitis C (HCV) is a curable cause of liver disease, typically treated by specialists. Access to specialists is limited in rural areas. Telemedicine between generalists and specialists could yield outcomes comparable with care provided by specialists in face-to-face (FTF) encounters. To assess the effectiveness of HCV treatment through telemedicine compared with usual care, as measured by sustained virologic response (SVR). Methods: We searched MEDLINE, the Cochrane Library, ClinicalTrials.gov, the Database of Abstracts of Reviews of Effects, and Excerpta Medica DataBASE from inception to March 2018. We included Randomized Controlled Trials (RCTs) and cohort studies comparing telemedicine in rural settings to FTF encounters with specialists in treating HCV. Studies reported cure as measured by SVR. We did not apply any exclusion criteria. At least 2 independent researchers used PRISMA guidelines to extract data. We used a modified Newcastle-Ottawa Scale and the Cochrane Collaboration Tool for Assessing Risk of Bias to assess observational studies and RCTs. We used a random-effects model to calculate pooled odds ratios (OR). The primary outcome was clinical cure. Cure was defined as SVR at 12 weeks after completion of treatment. Results: Of 1, 211 potentially eligible studies, 10 studies, representing 43, 117 subjects, met inclusion criteria. Pooled analysis showed no difference in the odds of achieving SVR when comparing telemedicine to FTF specialist care (OR 1.01 [95% CI 0.78–1.30]). This result was robust across sensitivity analyses, including restriction to patients who completed treatment (OR 0.78 [95% CI 0.43–1.43]), exclusion of outliers, and exclusion of abstracts. There was significant heterogeneity [ P = 0.003, I 2 = 64]. Conclusion: In rural areas with limited access to specialists, care provided by telemedicine-supported generalists is as effective as FTF specialist care in achieving cure of HCV. Telemedicine is a viable option to expand access to HCV care in rural settings. Disclosures: All authors: No reported disclosures.